High-speed photometry of faint cataclysmic variables – IX. Targets from multiple transient surveys. Issue 2 (12th April 2019) - Paterson, K; Woudt, P A; Warner, B; Breytenbach, H; Gilligan, C K; Motsoaledi, M; Thorstensen, J R; Worters, H L
Abstract: We present high-speed photometric observations of 25 cataclysmic variables detected by the All Sky Automated Search for Super-Novae, the Mobile Astronomical System of the TElescope-Robot, and the Catalina Real-Time Transient Survey. From these observations we determine 16 new orbital periods and 1 new superhump period. Two systems (ASASSN-14ik and ASASSN-14ka) have outburst periods of approximately 1 month, with a third (ASASSN-14hv) having outbursts approximately every 2 months. Included in the sample are 11 eclipsing systems, one probable intermediate polar (ASASSN-15fm), 1 SW Sex-type star (MLS 0720+17), 1 WZ Sge-type star (ASASSN-17fz), and one system showing different photometric and spectroscopic periods (ASASSN-15kw).